Machined versus rough surface implants, a clinical study: 36-month follow-up - Arismendi, Jorge Alberto; Mesa, Ana Lucía; García, Luz Piedad; Salgado, Juan Fernando; Castaño, Catalina; Mejía, Richard (Revista Facultad de Odontología Universidad de Antioquia, 2010)
Introduction: the implant surface affects the clinical response in terms of osseointegration and should be evaluated in the long term. In the last years, literature has strongly recommended the use of modified surface implants, in order to improve osseointegration. The primary stability is essential to obtain osseointegration and it depends on the micro and macro characteristics of the implant and bone structure. The usage of active surfaces is an advantage, but it does not modify the bone density. The aim of this study is to undertake a clinical and radiographic evaluation between two different groups of implants, machined versus modified surfaces. Methods: a 24 to 36 months clinical and radiographic follow-up was done to two groups of Lifecore® implants, one group with 30 machined implants (Super CAT®), and the other one with 30 modified surface (RBM®) external hex connection and screw type implants. Measurements were taken to determine the bone crest behavior using the implant platform as reference at 24-36 months of function and were compared with the 12 months measurements. Results: in machined implants at 24-36 months, the average marginal bone loss was 1.5 mm. In modified surface implants at 24 months, the average marginal bone loss was 1.4 mm, and at 36 months, the loss was 1.5 mm. Conclusions: there are no statistical significant differences between the two groups of machined and modified implant surface, for single tooth restoration, as it relates to clinical and radiographic follow up.